The Prevalence of Tooth Wears Among (18-25) Years Old College Students in Sulaimani City - Mohammad, Dena N.; Garib, Balkees Taha (Sulaimani Journal for Pure and Applied Sciences, 2012)
Non-carious loss of tooth structure is considered the 4th dimension risk factor for aesthetic, function and longevity of human dentition after acute trauma, caries and periodontal disease The aim of this study was to determine the prevalence and risk indicators for tooth wear in (18- 25) years in Sulaimani city. A total of 500 randomly selected college students were examined for tooth wear. The data were collected by means of a questionnaire about the history of possible causative factors and a clinical examination using Smith and Knight’s index on occlusal/incisal, buccal and lingual/palatal surfaces. Mild tooth wear (score 1) was present in 63.4%, while only 0.4% had lesions extending up to the dentine. There were 36.2% without tooth wear, there is no evidence of score 3 or score 4. Incisal edges of both lower and upper teeth were the most affected site (75.51%). Occlusal problem was the most common predisposing factor (72.73%). Tooth wear defect did not form an urgent problem at 18-25 years aged group, there was only minimal enamel loss (63.4%, score 1) that attributed mainly to occlusal problems.
Keywords: Tooth wear; enamel loss